Impact of a workshop on medical students’ knowledge and attitude towards quality improvement in health care: A quasi-experimental study - Taleb, Rim; Abdallah, Rawan; Abou Chahine, Rima; El Rawas, Sara; Alwan, Zouhour; Mallah, Ibrahim (Journal of University Teaching and Learning Practice, 2025)
Quality improvement (QI) is any structured process aiming at improving patient safety, clinical effectiveness or patients’ experiences of healthcare. Literature reveals the importance of integrating QI into the medical curriculum. The faculty of medicine at Beirut Arab University (BAU) in Lebanon has introduced QI education in the curriculum to the fifth-year medical students since 2017. In Lebanon, little is known about the attitudes and knowledge of medical students towards the concepts of QI in health care. Therefore, this study aims to assess the knowledge and attitude of medical students at BAU towards QI. This was a longitudinal time-series quasi-experimental study performed on fifth-year medical students at BAU throughout the academic year 2020-2021. All fifth-year medical students were targeted, each group during their family medicine rotation. Assessment of the attitude and beliefs and knowledge of QI was done using the BASIC-QI tool. The intervention consisted of filling a questionnaire before the QI workshop, immediately after and 1 month after. As a result, the mean scores of each of the "Attitude and Beliefs Scale", and the "Knowledge of QI Scale" both showed an increase right after and one month after the QI session with statistically significant P-values of